Development of Sciatic Neuropraxia following Abdominal Surgery in 3 Giant Breed Dogs - Laura Marti; Julia P. Sumner (Case Reports in Veterinary Medicine)
This report describes the clinical course of three giant breed dogs (2 Great Danes and 1 Saint Bernard) that developed sciatic neuropraxia following successful surgical management of gastric dilatation and volvulus (GDV). All three patients received physical rehabilitation with varying degrees of success. Two patients died of unrelated causes within a year of their initial presentation. The third case recovered nerve function and is alive with minimal neurologic deficits at the time of publication. This paper is aimed at positing potential causes for this complication and highlighting the importance of proper management of giant-breed dogs during hospitalization. Special attention should be given in regards to intraoperative positioning and postoperative care including frequent walks or changes in positioning, deep kennel bedding, and physical therapy.